Pemberdayaan Masyarakat dalam Penerapan Teknologi Probio_FM pada Usaha Budidaya Itik Petelur di Lahan Sekitar Pesantren Daarul Hasanah - Sudirman Adibrata; Novyandra Ilham Bahtera; Fardhan Arkan; Rufti Puji Astuti (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The existence of pesantren today, apart from being an educational institution in the religious field, is also expected to be able to provide an example towards creativity, innovation, and entrepreneurship to students. The purpose of this service activity is to empower the application of probio_Fm technology in laying duck cultivation, transfer knowledge of laying duck cultivation, and build an entrepreneurial spirit for students and the community around the boarding school. The service method uses an active participatory approach, starting with preparation and socialization activities, training, mentoring in duck cultivation, harvesting, and data collection. Data analysis was carried out by qualitative descriptive analysis. The results show that the pesantren community has been empowered to apply probio_FM technology for duck cultivation, both through drinking water and feed. The application of probio_FM technology in the cultivation of laying ducks makes the cultivation method easy, does not cause odors around the pesantren environment, and egg productivity reaches 87.5%.